The coroner : [large type] a mystery - Dornbush, Jennifer, 1971- (Center Point Large Print, 2020)
"Summoned from her promising surgical career first to her estranged father's bedside, and then his post as medical examiner when his small town needs urgent help with a suspicious death, Emily Hartford discovers home is where the bodies are in this pitch perfect mystery debut"--Provided by publisher.